Strengthening Governance through Engaged Societies : Lessons from the Implementation of Poverty Reduction Strategies - Barbone, Luca; Sharkey, Katrina (World Bank, Washington, DC, 2012)
In December 1999, the Boards of the World Bank and the International Monetary Fund approved a new approach to their relations with low-income countries. The approach was centered around the development and implementation of Poverty Reduction Strategies (PRS), which are intended to be country-driven and medium- to long-term in perspective, comprehensive and results-oriented, partnership-oriented, and built on broad-based participation. Against this tall order of business, experience to date has been varied, and much debate is ongoing on whether the approach can be considered more than "old wine in new bottles." This paper-based on the results of a thorough review of the five-year implementation experience-examines the implementation of the PRS approach from the point of view of participation and accountability. For some 50 countries adopting the approach since 1999, it discusses the factors which can facilitate the development of accountability and participatory governance mechanisms. Lessons learned from distinct country circumstances are analyzed, arguing that ownership of the PRS depends on the way countries and their external donor partners handle real tensions in the relationship between country ownership on the one hand, and perceptions of internationally-driven prescriptions on the other. The central message of the paper is that in several countries the PRS initiative has helped open up societies to forms of dialogue and contestability not previously experienced in-country or observed by external partners. This positive outcome, however, has been largely influenced by the extent to which the PRS process has reinforced existing trends and strengthened institutions already prone to open discussion of policy choices. The paper also shows that even in the best cases change has, to date, been largely in the area of process and that impact of participatory governance on policymaking, while emerging, is still a work in progress. The paper concludes with recommendations for how developing country societies might sustain real achievements in participatory governance and domestic accountability going forward, with external partners playing a key supportive role through harmonization and alignment.